EVALUASI KINERJA PELAYANAN PUBLIK DI LINGKUNGAN KANTOR CAMAT MANDAH KABUPATEN INDRAGIRI HILIR - jurnalmap map; Ika Purwanti; Kodrat Sunyoto; Arini Sulistyowati (MAP (Jurnal Manajemen dan Administrasi Publik), 2021)
The purpose of this research is to describe the performance of public services in the District Office of Mandah District, Indragiri Hilir Regency. The results of research on public service performance consists of: work results, leadership, work skills, cooperation, discipline. The quality of work in 2019 is around 80% of the 100% target, this is due to some activities which cannot be carried out due to technical problems. The quantity of work completes work on time and in accordance with established standards. Leadership in mobilizing and directing subordinates and providing encouragement, enthusiasm and support to employees is quite good and firm. Work skills of employees according to their respective fields and in accordance with their duties and functions. Cooperation in completing the tasks and activities of the sub-district office, the formation of an activity committee team and always supports all work programs so that work targets can be achieved.